PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON EQUITY PADA PT. KALBE FARMA TBK PERIODE 2014-2024 - Kania Dwi Candra; Hasanudin Hasanudin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of Current Ratio and Debt to Equity Ratio on Return on Equity of PT Kalbe Farma Tbk for the 2014–2024 period, either partially or simultaneously. The research method used is quantitative with a causal associative approach. The data utilized were secondary data consisting of income statements and statements of financial position from PT Kalbe Farma Tbk over an 11-year period. Data analysis was conducted using SPSS version 26, and testing included descriptive statistics, classical assumption test, multiple linear regression, coefficient of determination, partial hypothesis test (t-test), and simultaneous test (f-test). The results show that partially the Current Ratio has no effect on Return on Equity, with a tcount of 0.037 < ttable of 2.30600 and a significance value of 0.972 > 0.05. The Debt to Equity Ratio also has no effect on Return on Equity, with a tcount of 1.158 < ttable of 2.30600 and a significance value of 0.280 > 0.05. Simultaneously, Current Ratio and Debt to Equity Ratio have a significant effect on Return on Equity, evidenced by an Fcount of 4.529 > Ftable of 4.46 with a significance value of 0.048 < 0.05. The coefficient of determination indicates that the Current Ratio and Debt to Equity Ratio simultaneously contribute 53.10% to Return on Equity, while the remaining 46.90% is influenced by other variables not examined in this study. Keywords: Current Ratio, Debt To Equity Ratio, and Return on Equity.